Altered CO2 sensitivity of connexin26 mutant hemichannels in vitro. Issue 22 (24th November 2016) - de Wolf, Elizabeth; van de Wiel, Joseph; Cook, Jonathan; Dale, Nicholas
Abstract: Connexin26 (Cx26) mutations underlie human pathologies ranging from hearing loss to keratitis ichthyosis deafness (KID) syndrome. Cx26 hemichannels are directly gated by CO2 and contribute to the chemosensory regulation of breathing. The KID syndrome mutation A88V is insensitive to CO2, and has a dominant negative action on the CO2 sensitivity of Cx26 WT hemichannels, and reduces respiratory drive in humans. We have now examined the effect of further human mutations of Cx26 on its sensitivity to CO2 . Mutated Cx26 subunits, carrying one of A88S, N14K, N14Y, M34T, or V84L, were transiently expressed in HeLa cells. The CO2 ‐dependence of hemichannel activity, and their ability to exert dominant negative actions on cells stably expressing Cx26 WT, was quantified by a dye‐loading assay. The KID syndrome mutation, N14K, abolished the sensitivity of Cx26 to CO2 . Both N14Y and N14K exerted a powerful dominant negative action on the CO2 sensitivity of Cx26 WT . None of the other mutations (all recessive) had a dominant negative action. A88S shifted the affinity of Cx26 to slightly higher levels without reducing its ability to fully open to CO2 . M34T did not change the affinity of Cx26 for CO2 but reduced its ability to open in response to CO2 . V84L had no effect on the CO2 ‐sensitivity of Cx26. Some pathological mutations of Cx26 can therefore alter the CO2 sensitivity of Cx26 hemichannels. The loss of CO2 sensitivity could contribute to pathology and consequent reduced respiratory drive could be an unrecognized comorbidity of these pathologies. Abstract : Connexin26 (Cx26) mutations underlie human pathologies ranging from hearing loss to keratitis ichthysosis deafness (KID) syndrome. We show that some of these mutations reduce or abolish the sensitivity of the hemichannel to CO2 .